PELATIHAN PENGOLAHAN LIMBAH TEMPURUNG KELAPA SEBAGAI BAHAN BAKAR ALTERNATIF DI KECAMATAN PARUNG PANJANG, BOGOR - Dalimunthe, Yusraida Khairani (Jurnal Abdi Masyarakat Indonesia (JAMIN), 2025)
Everyday living relies heavily on energy. However, the availability of non-renewable energy sources is dwindling over time, raising the likelihood of their demise in the future. As a result, we must create new renewable energy sources from garbage, ensuring the proper use of waste while also supporting environmental conservation initiatives. We have the potential to process coconut shells into briquettes as an alternative fuel source due to their increased calorific value compared to other biomass types. We conducted this community service activity by training 17 housewives from Beverly Lake Housing in Parung Panjang, Bogor. The course will educate participants on how to convert coconut shell waste into briquettes using a simple process. The training method consists of both material delivery and hands-on practice manufacturing briquettes. The outcomes of the activity revealed that 100% of participants believed that this exercise was extremely effective in enhancing their understanding of processing coconut shell waste into briquettes. We aim to empower the community through this program to convert coconut shells, previously considered waste, into alternative fuels that not only replace oil and gas but also generate economic value for small companies.